Variability in Temporal Characteristics of the South Eastern Indian Ocean Pygmy Blue Whale Song - Capri D. Jolliffe; Robert. D. McCauley; Alexander N. Gavrilov (Animal Behavior and Cognition, 2023)
The temporal characteristics of whale song are considered to be amongst the most stable elements of song production, though very few studies have looked at the timing of discrete sounds or the silences between them. This study indicates that the temporal characteristics of the song of the southeast Indian Ocean pygmy blue (SEIOPB) whale are highly variable. While the song repetition interval, or inter-song interval (ISI), appeared to remain consistent within a song event, defined as a consistent bout of singing presumed to come from an individual animal, it was found to be variable between song events. Song structure was a confounding factor in the analysis of variability in ISI with songs comprised of longer phrases naturally having a longer song repetition interval. The songs of the SEIOPB whale are characteristic of the species with only three primary song types. The three-unit song (units I, II and III) has the longest mean ISI of ~ 200 s, approximately twice that of songs composed of only two units (II and III) at a mean of ~ 100 s ISI which is approximately twice the ISI of a one-unit song (unit II only). The results of this study suggest that variability in ISI cannot be attributed to change in one element of a song but is driven by temporal changes in all elements of the song including phrase structure, unit duration and the length of the intervals between song units. Thus, the temporal characteristics of blue whale song appear to be under the control of the animal and may vary between individual whales, and within songs of an individual. It is concluded that the temporal characteristics of song potentially encode contextual information about the singer and may be influenced by audience effects, including audience composition and singer density.